Human Rights Due Diligence as a Tool to Prevent Human Rights Violation by TNCs: An Assessment of the Current Regulations - Joel Niyobuhungiro (Business and Human Rights Law & Policy, 2025)
This paper explores the role of Human Rights Due Diligence (HRDD) as a tool to prevent human rights violations by Transnational Corporations (TNCs). Despite their contributions to economic development, TNCs often engage in activities that undermine fundamental human rights. This study evaluates the effectiveness of HRDD frameworks, focusing on the UK Modern Slavery Act (2015) and the French Duty of Care Law (2017). The research compares these regulations in terms of scope, corporate compliance mechanisms, and overall impact on mitigating human rights violations. Findings reveal that while these frameworks provide foundational steps toward accountability, significant gaps persist, such as limited applicability to certain corporations and insufficient reporting standards. This paper highlights the need for internationally binding instruments to regulate TNCs comprehensively and improve human rights compliance.